PERHITUNGAN ANGGARAN PENJUALAN DENGAN MENGGUNAKAN METODE KUADRAT TERKECIL PADA PT BLUE BIRD Tbk - Nanan Karyadi; Rita Rita (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2020)
Forecasting the calculation of risk that may occur in the future where the ups and downs of sales achieved by a company can be used as a measuring tool for the progress or decline of the company. In this study, the researcher wants to calculate the sales forecast of PT Blue Bird Tbk. for the 2020 period and want to see the difference in the sales budget with sales realization in 2015 to 2019 at PT Blue Bird Tbk. The research method used is qualitative by using secondary sales data of PT. Blue Bird from 2012-2019. From the results of the analysis of budget calculations using the quadrant method, it cannot be seen that the sales forecast in 2020 is 3,519,732,200,000, while the budget difference from 2012 to 2019 is as follows, for 2015 the difference between sales budget and a budget realization is 104.5%. For 2016, the difference is 98.07%. For 2017, the the budget is 92.43%. In 2018 budget of 100.32%. And in 2019 that the difference is 185,292,000,000 with a budget of 104.79%.